OPTIMALISASI KEMAMPUAN ISTIMA’ MELALUI LAGU DAN MUSIK ARAB: STUDI KASUS DI MADRASAH IBTIDAIYAH - Fitrah Nuur Lillah; Jumhur; Rendi Sabana (Universitas Islam Negeri Palopo, 2026)
This study aims to optimize students’ istima’ (listening) skills through the use of Arabic songs and music at MI Adabiyah 2 Palembang. The research background is based on the low listening ability of students, as revealed through initial observations, interviews, and pretest scores. The study employed a mixed-method design combining quantitative and qualitative approaches, involving 33 sixth-grade students as research subjects. Data were collected through observations, interviews, and tests (pretest and posttest) and were analyzed using the normality test, Paired Sample t-Test, and N-Gain Score. The results showed a significant improvement in students’ listening skills, indicated by an increase from the initially low pretest average of 57.03 to a posttest average of 79.39. The t-test revealed a significance value of <0.001, and the N-Gain Score of 0.5295 fell within the medium category, suggesting that the improvement was effective yet still required further reinforcement for optimal listening development. This improvement was largely influenced by the repetitive and rhythmic structure of Arabic songs, which helped students recognize sound patterns, strengthen vocabulary memory, and maintain better focus during listening activities. Therefore, Arabic songs and music are proven effective in enhancing students’ istima’ skills while creating a more active and enjoyable learning experience Penelitian ini bertujuan untuk mengoptimalkan kemampuan istima’ siswa melalui penggunaan media lagu dan musik Arab di MI Adabiyah 2 Palembang. Latar belakang penelitian ini didasarkan pada rendahnya kemampuan menyimak siswa yang ditunjukkan dari hasil observasi awal, wawancara, dan nilai pretest. Metode penelitian yang digunakan adalah mixed method dengan pendekatan kuantitatif dan kualitatif. Subjek penelitian terdiri dari 33 siswa kelas VI. Data dikumpulkan melalui observasi, wawancara, tes (pretest dan posttest), serta dianalisis menggunakan uji normalitas, Paired Sample t-Test, dan N-Gain Score. Hasil penelitian menunjukkan adanya peningkatan signifikan kemampuan istima’ siswa, ditandai dengan peningkatan nilai rata-rata pretest 57,03 menjadi posttest 79,39. Hasil uji t menunjukkan signifikansi <0,001 dan N-Gain Score sebesar 0,5295 dengan kategori sedang. Peningkatan ini terutama dipengaruhi oleh struktur lagu Arab yang repetitif dan ritmis. Dengan demikian, media lagu dan musik Arab terbukti efektif dalam meningkatkan kemampuan istima’ siswa serta menciptakan pembelajaran yang lebih aktif dan menyenangkan